MICHALSKI, Marcin (2019): Written Moroccan Arabic. A Study of Qualitative Variational Heterography, Poznań: Wydawnictwo Naukowe UAM, 216 pp. - MOSCOSO GARCÍA, Francisco (Al-Andalus Magreb, 2022)
No hay